Annual migrations, vertical habitat use and fidelity of Atlantic bluefin tuna tracked from waters off the United Kingdom - Thomas W. Horton; Francis C. T. Binney; Samantha Birch; Barbara A. Block; Owen M. Exeter; Francesco Garzon; Alex Plaster; David Righton; Jeroen van der Kooij; Matthew J. Witt; Lucy A. Hawkes (Scientific Reports)
Abstract Understanding the spatial ecology of commercially exploited species is vital for their conservation. Atlantic bluefin tuna (Thunnus thynnus, ABT) are increasingly observed in northeast Atlantic waters, yet knowledge of these individuals’ spatial ecology remains limited. We investigate the horizontal and vertical habitat use of ABT (158 to 241 cm curved fork length; CFL) tracked from waters off the United Kingdom (UK) using pop-up satellite archival tags (n = 63). Analyses reveal distinctive movements from the UK to the Bay of Biscay (BoB) and Central North Atlantic between September and December, and size-specific habitat preferences in May and July—all ABT < 175 cm CFL inhabiting the BoB and 73% of ABT ≥ 175 the Mediterranean Sea. All ABT tracked for more than 300 days (n = 25) returned to waters off the UK the following year, where most stayed (n = 22; 88%) and three continuing north with deployments ending off northwest Ireland. ABT mostly occupied waters between 0 and 20 m (daytime 49 ± 6% of time; nighttime 71 ± 6%). Vertical habitat use was coupled with illumination, mean depth occupied, maximum depth reached, and vertical movement rate increased during the daytime and when moons were brightest. These data provide valuable insights into the spatial ecology of ABT reoccupying northerly foraging areas following decades of absence.